1998
DOI: 10.1021/ic9807745
|View full text |Cite
|
Sign up to set email alerts
|

Iminoacylation. 1. Addition of Ketoximes or Aldoximes to Platinum(IV)-Bound Organonitriles

Abstract: The metal-mediated iminoacylation reaction of ketoximes or aldoximes upon treatment with the organonitrile platinum(IV) complexes trans-[PtCl(4)(RCN)(2)] proceeds under relatively mild conditions in acetonitrile (R = Me) or in chloroform (R = CH(2)Ph, Ph) to give trans-[PtCl(4)(NH=C(R)ON=CR(1)R(2))(2)] (R(1) = R(2) = Me; R(1)R(2) = C(4)H(8), R(1)R(2) = C(5)H(10), R(1)R(2) = (H)Ph, R(1)R(2) = (H)C(6)H(4)(OH)-o; 1-14) in 90-95% yield. All these compounds were characterized by elemental analyses (C, H, N, Cl, Pt)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
94
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 59 publications
12
94
1
Order By: Relevance
“…Thus, imines with very close structural characteristics being ligated to a metal center can exhibit even the opposite reactivity modes, for example, stabilization vs activation toward hydrolysis. 2 Recently we (see reviews 3 ) and others 4 found explicit evidence that platinum group metals, [5][6][7][8][9] rhenium, 10 gold, 11a,b or silver 11c centers provide enormous stabilization of the potentially unstable imines RR′CdNH, and these ligands can be "stored" without changes in the coordinated form under normal conditions for a prolonged time. Moreover, it appears that the formation of imines is one of the major driving forces for some reactions, e.g., condensation of complexed ammonia with ketones, 11 reductions of oximes, 12 oxidative dehydration of amines (e.g., at Fe, 13 Ru, 14,15 Os, 16 Re, 17 and Pt 18 centers), and nucleophilic additions to metal-bound nitriles.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, imines with very close structural characteristics being ligated to a metal center can exhibit even the opposite reactivity modes, for example, stabilization vs activation toward hydrolysis. 2 Recently we (see reviews 3 ) and others 4 found explicit evidence that platinum group metals, [5][6][7][8][9] rhenium, 10 gold, 11a,b or silver 11c centers provide enormous stabilization of the potentially unstable imines RR′CdNH, and these ligands can be "stored" without changes in the coordinated form under normal conditions for a prolonged time. Moreover, it appears that the formation of imines is one of the major driving forces for some reactions, e.g., condensation of complexed ammonia with ketones, 11 reductions of oximes, 12 oxidative dehydration of amines (e.g., at Fe, 13 Ru, 14,15 Os, 16 Re, 17 and Pt 18 centers), and nucleophilic additions to metal-bound nitriles.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Next, it is proposed that a nitrile molecule is released from the iminoacyl species IV to provide a putative benzimidic rhodium chelate V. [9] It can be postulated that two nitrile ligands then exchange a bidentate benzimidic acid from V releasing benzimidic acid VI that is readily tautomerized to benzamide. The present mechanistic proposal might also be supported by the observa- tion that nitriles were inert to the direct hydration with water in the absence of aldoximes.…”
mentioning
confidence: 99%
“…The reaction of trans-[PtCl 2 (NCR) 2 ] (R= Me, Et, CH 2 Ph) with HN=C(NHPh) 2 gave [PtCl-{HN=C(NC(NHPh)=NPh)R}(NCR)] derivatives, but if the reaction is carried out for a prolonged time upon heating in the presence of 4 equiv HN=C(NHPh) 2 , the nucleophilic attack proceeds on both nitriles to yield the corresponding [Pt{HN=C(NC-(NHPh) = NPh)R} 2 ] derivatives containing two bidentate 1,3,5-triazapentadiene ligands. [73] The cyanoguanidine complex cis- [78,79] alcohols, [80,81] hydroxamic acid, [82] amino acid esters [83] ). Of particular synthetic relevance is the preparation of oxazolines by preliminary reaction of trans-[PtCl 4 (NCEt) 2 ] with amino alcohols H 2 NCRR 1 CR 2 R 3 OH having varying degrees of substitution at the methylene groups, which fosters selective nucleophilic attack by the ÀNH 2 moiety, subsequent liberation of the hydroxo-functionalized amidines by reaction with dppe, and final conversion of the amidine to the oxazoline promoted by zinc(II) chloride according to Scheme 12.…”
Section: Reactions Ofmentioning
confidence: 99%